2019
DOI: 10.1371/journal.pone.0217772
|View full text |Cite
|
Sign up to set email alerts
|

Through the eye of a Gobi khulan – Application of camera collars for ecological research of far-ranging species in remote and highly variable ecosystems

Abstract: The Mongolian Gobi-Eastern Steppe Ecosystem is one of the largest remaining natural drylands and home to a unique assemblage of migratory ungulates. Connectivity and integrity of this ecosystem are at risk if increasing human activities are not carefully planned and regulated. The Gobi part supports the largest remaining population of the Asiatic wild ass ( Equus hemionus ; locally called “khulan”). Individual khulan roam over areas of thousands of square kilometers and the scale of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…We identified a set of 53 waterpoints which must be considered as having population-level importance (key waterpoints). At the same time, there is clear evidence that khulan are negatively impacted by human activities and livestock presence 34,43,55,56 . To ensure the long-term survival of the khulan in the South Gobi Region, key waterpoints should receive some form of protection that at a minimum ensures unlimited access by wildlife and limits disturbance to the surrounding habitat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified a set of 53 waterpoints which must be considered as having population-level importance (key waterpoints). At the same time, there is clear evidence that khulan are negatively impacted by human activities and livestock presence 34,43,55,56 . To ensure the long-term survival of the khulan in the South Gobi Region, key waterpoints should receive some form of protection that at a minimum ensures unlimited access by wildlife and limits disturbance to the surrounding habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Ground-truthing waterpoints. We opportunistically ground-truthed waterpoints for the presence of water or signs of recent khulan use (direct observations, tracks, dung) through: (1) field visits in March 2014 to inspect locations where many khulan tracks converged in the snowless winter of 2013/14, (2) field visits in July 2017 to waterpoints identified by the water finding algorithm that fell near our travel route, (3) photographs of waterpoints taken by a khulan with a camera collar at locations that overlapped with waterpoints identified by our water-finding algorithm 56 , and 4) a list of 45 waterpoints mapped by other researchers during field work 2013-2017 that overlapped with waterpoints identified by our water-finding algorithm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This point-in-time coincided with the normal birthing and mating period of kulan in the Altyn Emel source population, and the two mares which split off first had faecal oestrogen and progesterone levels which suggested that they were pregnant (Kaczensky et al, 2020). It is therefore quite possible that they left the group or stayed behind to give birth (Estep et al, 1995;Kaczensky et al, 2019).…”
Section: Movement Coordinationmentioning
confidence: 99%
“…However, further research based on rigorous study designs is required to understand the snow leopard's dependence on water across its habitat. Various methods can be used, including telemetry, high-intensity camera trapping with multiple units, and potentially even animal-mounted cameras (Rutz et al 2007;Kaczensky et al 2019).…”
mentioning
confidence: 99%